(untitled) (VERUM: Journal of Scientific Initiation, 2026)
This study analyzed the functional composition of native Cerrado species currently available in the seed market, highlighting the representativeness of different life forms. Based on public lists from community organizations and cooperatives, 145 species were identified and classified as either woody or herbaceous for comparative analysis. Statistical results revealed a significant predominance of woody species (95.5%) compared to herbaceous ones (4.5%), a pattern that does not reflect the natural functional diversity of the biome, where the herbaceous layer plays an important ecological role. The underrepresentation of herbaceous species may compromise restoration success by limiting functions such as soil cover and ecological resilience. This work reinforces the need for strategies that promote the inclusion of species from different ecological niches, fostering more comprehensive restoration efforts aligned with the characteristics of the ecosystem.